2017-JAPS-80 - F. Dadaşoğlu; R. Kotan (Journal of Animal and Plant Sciences, 2017)
The present study aims to identify Pectobacterium carotovorum, known as one of the most common soft rot causative agents using classical and molecular methods. Four different P. c. subsp. carotovorum strains from various hosts were obtained, two of which are causative agents of soft rot disease in potato and the other two in onion or pepper. These strains were confirmed as P. c. subsp. carotovorum by microbial identification system (MIS). In addition, BIOLOG system was used to identify these strains and the results were found to be inconsistent with those of microbial identification system. Test results of hypersensitive reaction (HR), pathogenity and pectolytic activity proved that all strains were pathogens. A number of biochemical and molecular analyses (16S rDNA and specific PCR) were conducted for identification and characterization. The strains were identified in genus level by means of 16S rDNA PCR method. Identified as P. c. subsp. carotovorum according to MIS results, these four strains were analysed in specific PCR tests and found to give 434 bp-long band with Y1-Y2 primers. This is the first study to reveal that these four strains are causative agents of soft rot disease in potato, onion and pepper in East Anatolia and also in Turkey.
Keywords: MIS and BIOLOG; PCR; Pectobacterium carotovorum; Soft rot